Modal Sosial dalam Perspektif Sosiologis: Tinjauan Sistematis terhadap Studi Empiris di Indonesia (2000–2024) - Herdiyanti Herdiyanti (Society, 2024)
Social capital is widely recognised as a cornerstone of inclusive development and social resilience in Indonesia. This article critically synthesises how Indonesian sociological research has conceptualised and applied social capital over the past two decades through a systematic review that adheres to PRISMA reporting standards. Searches in Google Scholar, Garuda, and DOAJ (1 January 2000 – 30 April 2024) returned 872 records; after de-duplication and screening, 41 peer-reviewed empirical articles were retained and analysed thematically. Four recurring themes emerge: (1) social capital as a driver of post-disaster community resilience; (2) its role in participatory development and village governance; (3) social capital’s ambivalent influence on exclusion and clientelism in urban–rural settings; and (4) the reconfiguration of social capital in digital environments during the COVID-19 pandemic. Theoretical orientation is dominated by Putnam (65.9 %), followed by Bourdieu (22.0 %) and Coleman (12.1 %). Although most studies highlight beneficial outcomes, only 19.5 % explicitly interrogate power, inequality, or dysfunctional social capital issues. The review confirms social capital’s explanatory reach yet underscores conceptual saturation and methodological conservatism, particularly an over-reliance on cross-sectional surveys and a paucity of intersectional or longitudinal designs. Future research should diversify theoretical frameworks, adopt mixed-methods and network-analytic approaches, and examine gendered and digital dimensions to advance Indonesian sociology’s understanding of social capital.